Indoor Environmental Quality of Residential Elderly Care Facilities in Northeast China - Jingyi Mu; Jian Kang (Frontiers Media S.A., 2022)
The indoor environmental quality is based on the indoor environmental performance of buildings, such as air temperature, lighting, and acoustics. These parameters have a specific impact on users' health and experience. This study explores the relationship between the indoor environment of residential elderly care facilities in cold regions and the sensitivity of the elderly to these facilities with the aim of improving the elderly care environment. This study measured the acoustic, lighting, and thermal environment in four residential elderly care facilities in Northeast China in spring, summer, autumn, and winter through a participant survey. In the residential elderly care facilities surveyed in this study, brightness and illuminance show a nonlinear relationship with lighting evaluation. With an increase in brightness and illuminance, the satisfaction of the lighting environment in different seasons first increases and then decreases. The relative humidity of the different types of rooms varies greatly in spring and less in winter. The average air quality score of the bedroom is higher than that of the activity room. The correlation between odor assessment and overall indoor environmental quality is very poor. The results of the questionnaire survey indicate that the participants were satisfied with the facilities' overall indoor environmental quality. This quality is affected by physical, environmental, and demographic factors. This study provides a reference for the design of other residential elderly care facilities.